Evaluasi Pelaksanaan Program Pembelajaran Pendidikan Jasmani di Kelas Khusus Olahraga SMP Negeri 1 Karawang Barat - Siti Yohanah; Resty Gustiawati; Ruslan Abdul Gani (Jurnal Ilmiah Wahana Pendidikan, 2023)
The establishment of special sports classes is also the initial stage that determines the success of organizing a special sports class program in which it is necessary to hold planning with adjustments to the educational components in schools so that the implementation of special sports classes can run well. The components that must be adjusted include: (1) Student criteria, (2) Curriculum, and (3) Facilities and infrastructure. Observation at SMP Negeri 1 West Karawang which has special sports classes, in Karawang Regency itself there are 6 schools with special sports classes in them. Of the several learning programs that have been applied to sports-specific class students, the implementation of learning given to learners is felt to be less adapted to the mastery of the learning program, with many obstacles such as the lack of organizedness of learners in responsibility for subjects such as assignments, students' understanding of learning programs that are limited to the purpose of understanding the expected learning movement practice Based on research and processing data that has been submitted from data and data analysis carried out by researchers, it can be concluded that the results of the evaluation process for the implementation of the physical education learning program at SMP Negeri 1 Karawang Barat in this special sports class have been carried out well and really help students in the Penjas learning process, students are much more understanding and still able to practice the movement Study. So even though they are more focused on their sports branch, they can still follow learning well and produce achievements.